Panel I: Agency Autonomy and the Unitary Executive - Stephen Breyer; Laurence Silberman; E. Donald Elliot; Terry Eastland (Washington University Law Quarterly, 1990)
I shall argue that we must separate two important issues: the first, "separation of powers," raises issues of constitutional law; and the second, "Presidential control of agency decision making," raises issues of fair and effective government.